THE ROLE OF THE INFORMATICS AND ENGLISH COMMUNICATIONS DEPARTMENT IN SUPPORTING THE ENREKANG DISTRICT GOVERNMENT PROGRAM "CITY OF GOLD" (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to analyze the role of Diskominfo in supporting the programs of Enrekang Regency Government as the "Golden City" through its function as a media disseminating information to the public. The research utilizes a descriptive research method with data collection techniques including observation, interviews, and document analysis. The system theory is used to understand the role of Diskominfo, while the excellent in public relations theory is used to understand the role of media publications by Diskominfo. The findings indicate that Diskominfo plays a vital role in providing effective communication channels between the government and the community in delivering information about the programs of Enrekang Regency Government as the "Golden City." Diskominfo acts as a media disseminating information, involving the use of various platforms such as social media, websites, and print publications. Through their role as information disseminators, Diskominfo is able to enhance public awareness of government programs and strengthen community participation and involvement in supporting the success of these programs. The results of this research provide recommendations to Diskominfo Enrekang Regency and related institutions to strengthen their role as effective information disseminators.